2015
DOI: 10.1590/01000683rbcs20140520
|View full text |Cite
|
Sign up to set email alerts
|

Estoques de Carbono e Nitrogênio e Densidade do Solo em Sistemas de Adubação Orgânica de Café Conilon

Abstract: RESUMO A produção de café conilon em sistemas de manejo orgânico tem aumentado no Estado do Espírito Santo. Porém, faltam informações sobre o impacto desse manejo sobre os estoques de carbono e nitrogênio do solo. Este trabalho teve como objetivo avaliar o efeito da adubação orgânica sobre os estoques de C e N e a densidade do solo (Ds) em agrossistema de café conilon. O experimento foi implantado em lavoura localizada no município de Linhares, ES, no delineamento em blocos casualizados com distribuição fatori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
(17 reference statements)
0
3
0
3
Order By: Relevance
“…The lowest bulk density in the surface layer of DC is due to the greater contribution of organic matter by the necromass (dead trees and litter) [26] in the surface layer. In general, organic residue has a lower specific weight compared to the mineral fraction [27].…”
Section: Bulk Densitymentioning
confidence: 99%
“…The lowest bulk density in the surface layer of DC is due to the greater contribution of organic matter by the necromass (dead trees and litter) [26] in the surface layer. In general, organic residue has a lower specific weight compared to the mineral fraction [27].…”
Section: Bulk Densitymentioning
confidence: 99%
“…Souza et al (2014) found no changes in the organic matter content of the 0 -20 cm soil layer after five years of surface applications of rates up to 36 t ha -1 of waste generated by the guava processing industry, consisting basically of seeds of the fruit. In the 0 -5 cm layer of an area of producing coffee plants, Silva et al (2015) found a linear increase in organic C content, and consequently of soil organic matter, in response to surface applications of organic compound containing coffee husk.…”
Section: Resultsmentioning
confidence: 90%
“…extract antioxidant compounds, used in the food, cosmetic and pharmaceutical industries (GARCIA and BIANCHI, 2015); as bedding in confinement facilities of animals (MATIELLO et al, 2010); and for power generation by direct burning, in industrial furnaces or in coffee bean dryers (SATER et al, 2011). However, for being a source of nutrients, in particular of K (HIGASHIKAWA; SILVA; BETTIOL, 2010), it is largely used in agriculture, as a substrate component for seedling production (ASSIS et al, 2011), in organic compost (SILVA et al, 2015), or mainly as organic fertilizer of coffee plants (FIDALSKI and CHAVES, 2010;FERNANDES et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Para alface foi confirmado os efeitos benéficos da adição de composto orgânico com aumento na massa e nos teores de nutrientes (ABREU et al 2010; SHAHEIN; AFIFI; ALGHARIB, 2014), sendo encontrado valores superiores a 40% na produtividade, em comparação ao controle (SEDIYAMA et al, 2016). Desta forma, o efeito residual da matéria orgânica adicionada pode ocorrer a longo prazo sobre culturas cultivadas em sucessão (DINIZ et al 2017;LANNA et al 2018) ou a médio e pequeno prazo sobre a cultura implantada após a adição do composto (CANDIAN;CARDOSO, 2015;SILVA et al 2015), conforme observados no acúmulo de massa nas plantas de T. triangulare e T. paniculatum (Tabelas 4 a 5).…”
Section: Resultsunclassified